2021
DOI: 10.1038/s41467-021-24999-5
|View full text |Cite|
|
Sign up to set email alerts
|

Somatic genetic rescue of a germline ribosome assembly defect

Abstract: Indirect somatic genetic rescue (SGR) of a germline mutation is thought to be rare in inherited Mendelian disorders. Here, we establish that acquired mutations in the EIF6 gene are a frequent mechanism of SGR in Shwachman-Diamond syndrome (SDS), a leukemia predisposition disorder caused by a germline defect in ribosome assembly. Biallelic mutations in the SBDS or EFL1 genes in SDS impair release of the anti-association factor eIF6 from the 60S ribosomal subunit, a key step in the translational activation of ri… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

7
71
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 55 publications
(78 citation statements)
references
References 66 publications
7
71
0
Order By: Relevance
“…In 1/6 cases, the patient with the i(7)(q) rearranged independently the normal chromosome 7 in a different clone. These findings strongly indicate that in SDS patients there is a peculiar karyotype instability, depending upon a mechanism/s not yet identified, that, through a striking and specific selective pressure, acts mainly on chromosomes 7 and 20 and drives to a somatic rescue of the clone, as recently shown by Tan and coworkers for del(20)(q) [16].…”
Section: Discussionsupporting
confidence: 67%
See 3 more Smart Citations
“…In 1/6 cases, the patient with the i(7)(q) rearranged independently the normal chromosome 7 in a different clone. These findings strongly indicate that in SDS patients there is a peculiar karyotype instability, depending upon a mechanism/s not yet identified, that, through a striking and specific selective pressure, acts mainly on chromosomes 7 and 20 and drives to a somatic rescue of the clone, as recently shown by Tan and coworkers for del(20)(q) [16].…”
Section: Discussionsupporting
confidence: 67%
“…Both these anomalies are predicted to result in more efficient ribosome biogenesis in the BM abnormal clone which may lower the risk of MDS/AML [ 10 , 11 ] and result in a milder haematological condition compared to SDS patients with other chromosome changes or with normal karyotype [ 13 15 ]. These conclusions were further supported by a recent paper concerning the benign effects of somatic mutations of EIF6 [ 16 ].…”
Section: Introductionsupporting
confidence: 68%
See 2 more Smart Citations
“…Hematopoietic colony-forming assays showed that EIF6 I13N and EIF6 A194T (EIF6 destabilization) and EIF6 N106S (disrupt EIF6 −60S ribosomal protein RPL23 interaction) mutations expressed in SBDS-deficient human CD34 + cells increased their myeloid and erythroid colony output, suggesting that EIF6 mutations increased their hematopoietic function. A subsequent study also reported similar loss of function EIF6 mutations in patients with SDS [28].…”
Section: New Molecular and Genetic Insights Into Shwachman−diamond Sy...supporting
confidence: 53%